Vasorelaxant Activity of (2S)-Sakuranetin and Other Flavonoids Isolated from the Green Propolis of the Caatinga Mimosa tenuiflora - Son, Ninh The; Gianibbi, Beatrice; Panti, Alice; Spiga, Ottavia; Bastos, Jairo Kenupp; Fusi, Fabio (Planta Medica, 2024)
Some in vitro and in vivo evidence is consistent with the cardiovascular beneficial activity of propolis. As the single actors responsible for this effect have never been identified, an in-depth investigation of flavonoids isolated from the green propolis of the Caatinga Mimosa tenuiflora was performed and their mechanism of action was described. A comprehensive electrophysiology, functional, and molecular docking approach was applied. Most flavanones and flavones were effective CaV1.2 channel blockers with a potency order of (2S)-sakuranetin > eriodictyol-7,3′-methyl ether > quercetin 3-methyl ether > 5,4′-dihydroxy-6,7-dimethoxyflavanone > santin > axillarin > penduletin > kumatakenin, ermanin and viscosine being weak or modest stimulators. Except for eriodictyol 5-O-methyl ether, all the flavonoids were also effective spasmolytic agents of vascular rings, kumatakenin and viscosine also showing an endothelium-dependent activity. (2S)-Sakuranetin also stimulated KCa1.1 channels both in single myocytes and vascular rings. In silico analysis provided interesting insights into the mode of action of (2S)-sakuranetin within both CaV1.2 and KCa1.1 channels. The green propolis of the Caatinga Mimosa tenuiflora is a valuable source of multi-target vasoactive flavonoids: this evidence reinforces its nutraceutical value in the cardiovascular disease prevention arena.
Keywords: Green propolis; (2S)-sakuranetin; Mimosa tenuiflora; CaV1.2 channels; KCa1.1 channels; Fabaceae